Phrynocephalus helioscopus saidalievi ssp. n. (Sauria, Reptilia) — новый подвид такырной круглоголовки из Ферганской долины - Сатторов, Т. (Вестник зоологии, 1981)
An analysis of the geographic variability of Phrynocephalus helioscopus for nine characters of five samplings from the Ferghana valley and Western Kazakhstan shows that the individuals from the Ferghana valley described as a new Ph. helioscopus saidaliewi ssp. n. subspecies are characterized by a longer tail, 17-22 scales across the cap, 14-16 labium scutella, blue colour of the tail from below and by some other characters.